Analysis of procedural sedation provided by pediatricians. Issue 1 (14th February 2013) - Monroe, Kimberly K.; Beach, Michael; Reindel, Rebecca; Badwan, Laura; Couloures, Kevin G; Hertzog, James H.; Cravero, Joseph P.
Abstract Background Pediatric procedural sedation outside of the operating room is performed by a variety of pediatric specialists. Using the database from the Pediatric Sedation Research Consortium (PSRC), patient demographics, medications used, diagnoses, complications, and procedures involved when pediatricians provided sedation in this cohort, were described. 'Pediatrician' was defined as a general pediatrician, cardiologist, endocrinologist, gastroenterologist, hematologist/oncologist, neurologist, pulmonologist or hospitalist. Methods Data were collected by the PSRC, a group of 35 institutions dedicated to improving sedation care for children. Members prospectively enrolled consecutive patients who received sedation or anesthesia for diagnostic or therapeutic procedures. Data on demographics, primary diagnoses, procedures, medications, interventions, and complications were collected and stored on a Web‐based data collection tool. Results A total of 12 113 sedations performed by pediatricians were submitted from 1 July 2004 to 31 December 2008, compared to 119 665 cases performed by non‐pediatricians. Pediatrician patients were more frequently non‐emergency American Society of Anesthesiologists (ASA) class I or II, aged 2–8 years old, with a neurologic primary diagnosis, being sedated for a radiologic procedure with a sedative. Distraction techniques were used more frequently in the pediatrician group (11.9% vs 3.1%). The most common complication encountered was inadequate sedation, which occurred 2.2% of the time. Conclusions Pediatricians sedate for a variety of patients within the PSRC, but the patients tended to be younger, predominately ASA class I or II, non‐emergency, and undergoing non‐painful procedures when compared to non‐pediatrician providers. The patient demographics, medications used, diagnoses, complications, and procedures involved varied between the groups significantly. Complication rates were similar between the groups.